SAFETY AND EFFICACY OF PROTRACTED USAGE OF ORAL ANTIDIABETIC DRUGS IN TYPE-2 DIABETES MANAGEMENT - RAJA ADITHYA B; NISMA NAYEEM; ASHOK VARDHAN N; DURGA B (Asian Journal of Pharmaceutical and Clinical Research, 2025)
This review paper explores the impact of prolonged usage of oral antidiabetic drugs, particularly focusing on the therapeutic benefits and adverse effect associated with long-term consumption of these medications. Diabetes mellitus is becoming increasingly common worldwide, with 415 million adults diagnosed in 2015 and an anticipated increase to 642 million by 2040. Successfully treating type 2 diabetes typically involves a multi-faceted approach, targeting both insulin resistance and impairing the function of endocrine beta-cell using multiple medications. Although metformin is commonly regarded as the primary oral medication for diabetes management, it may not always provide adequate control, prompting the need for supplementary therapies to enhance its efficacy. Among the various oral antidiabetic agents available, sulfonylureas, such as glimepiride, remain a popular choice as a second-line add-on to metformin, particularly in Indian clinical settings. Compared to conventional sulfonylureas like glibenclamide, modern sulfonylureas like glimepiride have shown improved outcomes and better safety profiles. Glimepiride has been extensively studied and has a large body of evidence supporting its use. Nevertheless, antidiabetic medications have shown limited success in attaining ideal blood sugar control, with merely 41% of individuals reaching the intended goals. Additionally, questions have been raised regarding the possible harmful effects and adverse reactions of these drugs, such as increased body weight, decreased bone density, and heightened risk of heart-related issues. The use of sulfonylureas has been linked to heightened risks of low blood sugar, increased body mass, and harm to the cardiovascular system. In contrast, usage of metformin may lead to digestive system discomfort. Despite potential risks, the advantages of these drugs, including better blood sugar management, kidney protection, and fewer diabetes-related complications, generally surpass the possible drawbacks when used carefully. In response to these issues, scientists have investigated alternative strategies to reduce long-term use of antidiabetic medications.